How misconduct in business contributes to understanding the supply side of corruption in international business. Issue 3 (12th October 2019) - Ertz, Myriam; Karakas, Fahri; Stapenhurst, Frederick; Draman, Rasheed; Sarigöllü, Emine; Jo, Myung-Soo
Abstract : Purpose: This study aims to offer a better understanding of supply side of bribery and corruption in an international business perspective by conceptualizing it in the narrower concept of misconduct in business (MIB) derived from the deontological perspective to business ethics. Design/methodology/approach: The authors use a case study methodology of professionals working within Canadian mining multinational corporations operating in Africa. The authors conducted 2 focus groups, 25 in-depth interviews, document search and an open-ended questionnaire to 15 professionals. Further, they drew on a combination of the classic relationalist sociological framework and its recent revision, that they named the relationalism-substantialism framework to analyze the data. Findings: The triangulated empirical data show that the reason why MIB in the form of bribery supply occurs is not exclusively tied to any given perspective, whether the individual, the organization or the wider societal context. Rather, these different layers are tightly intertwined and interact with each other for the supply of bribery to occur. Originality/value: Although the three siloed perspectives of MIB have been studied in the literature, they have not been addressed in relation to one another, and even less with a relationalism-substantialism framework. Yet, this perspective contributes compellingly to the understanding of the supply side in bribery. The authors propose a net of conceptually related constructs that intervene in the process of bribery supply occurrence, namely relationality influenced by institutional dysfunctionality and conflation and substantiality through agency and culture.